Phylogenomics of North American cybaeid spiders (Araneae, Cybaeidae), including the description of new taxa from the Klamath Mountains Geomorphic Province - Marshal Hedin; Martín J. Ramírez; Rodrigo Monjaraz-Ruedas (ZooKeys)
The systematics of humble-in-appearance brown spiders (“marronoids”), within a larger group of spiders with a modified retrolateral tibial apophysis (the RTA Clade), has long vexed arachnologists. Although not yet fully settled, recent phylogenomics has allowed the delimitation and phylogenetic relationships of families within marronoids to come into focus. Understanding relationships within these families still awaits more comprehensive generic-level sampling, as the majority of described marronoid genera remain unsampled for phylogenomic data. Here we conduct such an analysis in the family Cybaeidae Banks, 1892. We greatly increase generic-level sampling, assembling ultraconserved element (UCE) data for 18 of 22 described cybaeid genera, including all North American genera, and rigorously test family monophyly using a comprehensive outgroup taxon sample. We also conduct analyses of traditional Sanger loci, allowing curation of some previously published data. Our UCE phylogenomic results support the monophyly of recognized cybaeids, with strongly supported internal relationships, and evidence for five primary molecular subclades. We hypothesize potential morphological synapomorphies for most of these subclades, bringing a robust phylogenomic underpinning to cybaeid classification. A new cybaeid genus Siskiyu gen. nov. and species Siskiyu armilla sp. nov. is discovered and described from far northern California and adjacent southern Oregon and a new species in the elusive genus Cybaeozyga, C. furtiva sp. nov., is described from far northern California.